Iso speed evaluation of digital cameras - Lee, Mervin Zhen Yuan. (2010)
Digital cameras have already overtaken traditional film cameras in the current technological era. The design for digital cameras is modeled after the traditional film cameras as close as possible. Certain factors like aperture and shutter speed could be almost similar to the film cameras. The bigger challenge is to model film speed into ISO speed settings in digital camera. Hence, the accurate representation of film speed on digital cameras is disputable. This project aims to create a program that is able to compare the ISO values of cameras of 3 manufacturers (Canon, Nikon and Olympus) with the actual ISO value measured from the image taken using these cameras. The results are then analyzed to determine the accuracy of the ISO values specified on the respective cameras.